A netnographic study on perceptions of consuming virtual food - Rokhshad, T.; Tan, Ai Ling *
Virtual technology is re-ontologizing our world by creating new realities. Virtual tourism is an area that receives particular attention from software developers and consumers. Virtual tourism experiences involve all the aspects of actual tourism, such as leisure and recreational activities, food, and sex. Since food is one of the essential components of both daily life and the tourism experience, studies on virtual food perception and experiences are very significant. Many pieces of research have been conducted on virtual food experiences in various fields, such as psychology, food and computer sciences. Relatively speaking, however, virtual food has been neglected by tourism scholars. This paper attempts to explore the perception of virtual food consumption by applying netnography and a qualitative content analysis approach under the social constructivism paradigm. Sociological perspectives of the acceptance of virtual food consumption are analysed in this paper. Data was collected from comments on a video about virtual food that was shared on Facebook. The data set was analysed using the thematic method. The key findings of this study reveal that the idea of virtual food technology is entirely accepted by most people; they are looking forward to experiencing it and, at the same time, they suggest implementing it in sustainable development. These suggestions include the future use of virtual food; how it can be used to help with health conditions, solving hunger issues and obesity; and the potential to spend less on food products. Although many were in favour of the idea of virtual food, some respondents did not agree with investing in this kind of project.